PENGEMBANGAN INSTRUMEN EVALUASI UJI KOMPETENSI KEAHLIAN (UKK) ADMINISTRASI PERKANTORAN DI SMK - Suranto, Suranto; Muhyadi, Muhyadi; Mardapi, Djemari (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2014)
Penelitian ini bertujuan mengembangkan instrumen yang cocok untuk melakukan evaluasi penyelenggaraan kegiatan UKK administrasi perkantoran di Sekolah Menengah Kejuruan (SMK). Penelitian pengembangan ini mencakup empat tahapan utama, yaitu tahap pendahuluan, tahap perencanaan dan pengembangan, tahap uji coba evaluasi dan revisi, serta tahap implementasi. Teknik pengumpulan data penelitian ini menggunakan teknik focus group discussion, angket/kuesioner, wawancara, observasi, dan studi dokumen. Analisis data dengan responden siswa menggunakan program Lisrel 8.51 dan data dengan responden guru dianalisis menggunakan SPSS 17.00 for Windows. Hasil penelitian ini sebagai berikut: (1) komponen penyelenggaraan UKK mencakup: (a) kolaborasi sekolah dengan asosiasi profesi dan DU/DI; (b) kinerja asesor; (c) sarana prasarana penunjang UKK; (d) sikap siswa terhadap UKK; (e) informasi capaian kompetensi siswa; dan (f) pengakuan legal asosiasi profesi dan DU/DI. (2) hasil pengujian menunjukkan: (a) instrumen dengan responden siswa berdasarkan data uji coba pada tahap implementasi, seluruh instrumen valid, reliabel, dan memenuhi syarat sebagai model yang fit; (b) instrumen dengan responden guru pada tahap implementasi menunjukkan seluruh butir instrumen memiliki nilai validitas > 0,30 dan memenuhi kriteria KMO > 0,50 serta koefisien reliabilitas Î± > 0,70. Kata kunci: pengembangan, instrumen evaluasi, uji kompetensi keahlian ______________________________________________________________DEVELOPING AN EVALUATION INSTRUMENTS OF THE OFFICE ADMINISTRATION EXPERTISE COMPETENCY TEST IN VOCATIONAL HIGH SCHOOLSAbstract This study aims to develop an evaluation instruments which is appropriate to evaluate the implementation of the Expertise Competency Test (ECT) for the Office Administration Expertise in vocational high schools (VHSs). This developmental research includes four major stages, namely the preliminary stage, the planning and development stage, the trial stage for evaluation and revision, as well as the implementation stage. For the data collection techniques, this study used focus group discussion, questionnaire, interview, observation, and document study. The data analysis for the students' responds was carried out using Lisrel Program version 8.51., while that for the teachers' responds was carried out using SPSS version 17.00 for Windows. The results of the study are as follows. 1) the components of the ECT activities include: (a) the collaboration of the schools and professional associations and the Business Sector/Industrial Sector (BS/IS); (b) the assessors' performances; (c) infrastructure facilities supporting the ECT; (d) students' attitudes towards the ECT; (e) the information about the students' attainments, and (f) the legal recognition from professional associations and the Business Sector/Industrial Sector or the BS/IS. 2) The study showed that: (a) based on the tryout data in the implementation stage, all items in the instrument with student respondents were valid, reliable, and qualified as a fit model; (b) on the implementation stage, all items in the instrument with teacher respondents had the validity value > 0.3 and, therefore, met the criteria of KMO >0.5 and the coefficient of reliability Î± > 0.70.Keywords: development, evaluation instrument, expertise competency test